2011
DOI: 10.1111/j.1532-5415.2011.03483.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Older Latino and Asian Immigrants with Limited English Proficiency

Abstract: Older Latinos and Asians with LEP are at higher risk for poor physical and mental health outcomes and inadequate health care. Healthcare systems should consider strategies to address the language needs of older immigrants to reduce the effect of linguistic disparities on access to care and ultimately to improve health status for these vulnerable populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 26 publications
3
77
2
Order By: Relevance
“…Prior studies in non-CKD populations have described suboptimal processes of care among adults with limited English proficiency such as poorer glycemic control among patients with diabetes. 26,27 In our study, we found no evidence to suggest that non-English speakers were at higher risk for progressing to ESRD compared with English speakers. The CHN provides a wide range of interpreter services and health information in several foreign languages, and it is possible that these services reduced linguistic barriers to care in our diverse patient population.…”
Section: Discussioncontrasting
confidence: 85%
“…Prior studies in non-CKD populations have described suboptimal processes of care among adults with limited English proficiency such as poorer glycemic control among patients with diabetes. 26,27 In our study, we found no evidence to suggest that non-English speakers were at higher risk for progressing to ESRD compared with English speakers. The CHN provides a wide range of interpreter services and health information in several foreign languages, and it is possible that these services reduced linguistic barriers to care in our diverse patient population.…”
Section: Discussioncontrasting
confidence: 85%
“…The chronic illness variable was based on the presence of only four chronic diseases. As was suggested in previous research using CHIS data (Kim et al, 2010(Kim et al, , 2011, this is limiting as some important geriatric conditions were not included. There are also geographic limitations of the study as the data were collected from residents of California.…”
Section: Aging and Mental Healthmentioning
confidence: 94%
“…Most Asian Americans (74%) are foreign born, and half (48%) have limited English proficiency (LEP) (Pew Social & Demographic Trends, 2012), defined as speaking English less than “very well” (Agency for Healthcare Research and Quality, 2010). Among older Asian Americans, in addition to the known determinants of poor self-rated health such as advancing age, low levels of education, low income, and multiple chronic health conditions (Todorova et al, 2013; Zack, 2013), LEP is independently associated with disparities in both healthcare access and health status (Kim et al, 2011; Ponce, Hays, & Cunningham, 2006). …”
Section: Introductionmentioning
confidence: 99%